Analysis of the Strategy for Collecting Zakat, Infaq and Shodaqoh (ZIS) Funds at the Amil Zakat Muhammadiyah Institution (LAZISMU) Belitung Regency - Saputra, Epan; Sujatna, Yayat (Institut Agama Islam Yasni Bungo, 2024)
Strategy is a way to achieve goals. Through a good strategy, the expected achievement will be even better. Therefore the author raises the theme of this research, namely the Strategy for Collecting Zakat, Infaq and Shodaqoh (Zis) Funds Carried Out by the Muhammadiyah Zakat Amil Institute (Lazizmu) Belitung Regency. The purpose of this study is to find out the best strategy that can be implemented by the Amil Zakat Muhammadiyah Institute (Lazismu) in Belitung Regency in collecting zakat, infaq and shodaqoh (ZIS) funds, whether this strategy has an effect on increasing the receipts of zakat, infaq and shodaqoh funds (zis ) amil zakat Muhammadiyah (lazizmu) Belitung regency and what are the obstacles encountered in carrying out strategies for collecting zakat funds, infaq and shodaqoh (zis) ) amil zakat Muhammadiyah institution (lazismu) belitung regency. This research is a descriptive research with a qualitative approach. The data used are primary and secondary data, with data collection techniques of observation, interviews and documentation. While the method of data analysis uses descriptive analysis because in this study the author describes the collection of ZIS funds in Belitung Regency. The results of this study show that there are three strategies for your lazismu strategy in collecting zis funds, namely with zakat cards, infaq and kencleng boxes and digital fundraising.